Filmmaking practice and animals’ geographies: attunement, perspective, narration - Turnbull, J; Searle, A (SAGE Publications, 2021)
After being captured from the streets of Moscow, Laika was the first living creature to be sent into Earth’s orbit by the USSR in 1957. The 2019 film, Space Dogs, tells the story of Laika’s spectral return to Moscow, and searches for her ghosts in the city’s street dogs 60 years later. Combining archival material with contemporary documentary footage ‘filmed at dog’s level’, the film reanimates Laika’s spectral afterlives. Drawing on a series of in-depth conversations with the film’s directors, writers, and director of photography, we provide critical reflections on filmmaking practice for animals’ geographies. We offer a three-part typology which frames these contributions: attunement, which focuses on the affordances of filmmaking practice for attuning to the lives of nonhuman lifeworlds; perspective, which documents how filmmaking practice allows for more-than-human urban space to be viewed from alternative vantage points; and narration, which enables filmmakers to experiment with affective modes of representing animals’ lives, offering audiences alternative spatiotemporal experiences. Finally, we reflect on the potentials of filmmaking as a fruitful practice, method, and output for animals’ geographers.